Enhancing CRISPR/Cas9-mediated homology-directed repair in mammalian cells by expressing Saccharomyces cerevisiae Rad52. (November 2017) - Shao, Simin; Ren, Chonghua; Liu, Zhongtian; Bai, Yichun; Chen, Zhilong; Wei, Zehui; Wang, Xin; Zhang, Zhiying; Xu, Kun
Highlights: Co-expressing Rad52 enhances CRISPR/Cas9-mediated HDR on surrogate reporters. Rad52-Cas9 fusion enhances HDR at the surrogate reporter level. HDR-based genome editing in human HEK293T cells can be enhanced by Rad52 co-expression and Rad52-Cas9 fusion. Rad52-Cas9 fusion enhances the HDR-based modification of the IGF2 gene in porcine PK15 cells. Abstract: Precise genome editing with desired point mutations can be generated by CRISPR/Cas9-mediated homology-directed repair (HDR) and is of great significance for gene function study, gene therapy and animal breeding. However, HDR efficiency is inherently low and improvements are necessitated. Herein, we determined that the HDR efficiency could be enhanced by expressing Rad52, a gene that is involved in the homologous recombination process. Both the Rad52 co-expression and Rad52-Cas9 fusion strategies yielded approximately 3-fold increase in HDR during the surrogate reporter assays in human HEK293T cells, as well as in the genome editing assays. Moreover, the enhancement effects of the Rad52-Cas9 fusion on HDR mediated by different (plasmid, PCR and ssDNA) donor templates were confirmed. We found that the HDR efficiency could be significantly improved to about 40% by the combined usage of Rad52 and Scr7. In addition, we also applied the fusion strategy for modifying the IGF2 gene of porcine PK15 cells, which further demonstrated a 2.2-fold increase in HDR frequency. In conclusion, our data suggests that Rad52-Cas9 fusion is a good option for enhancing CRISPR/Cas9-mediated HDR, which may be of use in future studies involving precise genome editing.